Evaluation of Disaster Preparedness Based on Simulation Exercises: A Comparison of Two Models. (4th February 2016) - Rüter, Andres; Kurland, Lisa; Gryth, Dan; Murphy, Jason; Rådestad, Monica; Djalali, Ahmadreza
Abstract: Objective: The objective of this study was to highlight 2 models, the Hospital Incident Command System (HICS) and the Disaster Management Indicator model (DiMI), for evaluating the in-hospital management of a disaster situation through simulation exercises. Methods: Two disaster exercises, A and B, with similar scenarios were performed. Both exercises were evaluated with regard to actions, processes, and structures. After the exercises, the results were calculated and compared. Results: In exercise A the HICS model indicated that 32% of the required positions for the immediate phase were taken under consideration with an average performance of 70%. For exercise B, the corresponding scores were 42% and 68%, respectively. According to the DiMI model, the results for exercise A were a score of 68% for management processes and 63% for management structure (staff skills). In B the results were 77% and 86%, respectively. Conclusions: Both models demonstrated acceptable results in relation to previous studies. More research in this area is needed to validate which of these methods best evaluates disaster preparedness based on simulation exercises or whether the methods are complementary and should therefore be used together. ( Disaster Med Public Health Preparedness . 2016;10:544–548).